Review of species of Limotettix (Scleroracus) Van Duzee, 1894 (Homoptera: Auchenorrhyncha: Cicadellidae: Deltocephalinae) of the fauna of Russia with description of a new cryptic species from Sakhalin - Tishechkin, Dmitri Yu. (Zootaxa, 2019)
Illustrated descriptions of 10 species of Limotettix (Scleroracus) of the fauna of Russia with data on host plants, male calling signals, and distribution are given. L. (S.) falco sp. n. from Southern Sakhalin is described, the synonymy L. (S.) transversus (Fallén, 1826) = Scleroracus fasciatus Kuoh, 1985, syn. n. is established. Evolution of the subgenus in Palearctic, and acoustic communication channels segregation in L. (Scleroracus) are discussed.